Analisis Hadis”Berdusta Atas Nama Nabi Muhammad Saw” dalam Konteks Empat Kompetensi Guru - Husna Husna; Syabuddin Syabuddin; Fauzan Fauzan (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2025)
The hadith of the Prophet Muhammad (peace be upon him), "Whoever lies about me intentionally, let him take his place in Hell" (Narrated by Bukhari and Muslim), is a stern warning to maintain honesty, especially for educators. This study aims to examine this hadith in relation to a teacher's competence. Hadith, as a source of Islamic teachings after the Qur'an, serves as a guideline in various aspects of life, including education. Teachers as educators are required to convey knowledge correctly, without reducing or misleading the teachings. This study uses a library research approach and content analysis techniques to examine the meaning and relevance of the hadith. The results of the study indicate that this hadith has a close relationship with four teacher competencies, namely pedagogical, professional, personality, and social. This hadith emphasizes the importance of integrity, honesty, and responsibility in carrying out a teacher's duties, while also making him a role model for students.